Antiemetic efficacy and safety of granisetron or palonosetron alone and in combination with a corticosteroid for ABVD therapy-induced nausea and vomiting - Mayako Uchida; Tsutomu Nakamura; Kojiro Hata; Hiroyuki Watanabe; Yasuo Mori; Koji Kato; Kenjiro Kamezaki; Katsuto Takenaka; Motoaki Shiratsuchi; Keiko Hosohata; Toshihiro Miyamoto; Koichi Akashi (BMC, 2018)
Abstract Background Antiemetic effects and safety of granisetron or palonosetron alone and in combination with a corticosteroid against chemotherapy-induced nausea and vomiting (CINV) were retrospectively evaluated in patients with Hodgkin lymphoma receiving adriamycin, bleomycin, vinblastine, and dacarbazine (ABVD) therapy. Methods A total of 39 patients were eligible for this study. Before ABVD therapy, granisetron or palonosetron was intravenously administered with or without a corticosteroid (dexamethasone or hydrocortisone) and aprepitant. The proportions of patients with complete control (CC) during the overall (0-120 h after the start of ABVD therapy), acute (0-24 h) and delayed (24-120 h) phases were evaluated. CC was defined as no vomiting and no use of antiemetic rescue medication with only grade 0-1 nausea. Results Granisetron and palonosetron were administered in 21 and 18 patients, respectively. The CC rate during the acute, delayed and overall phases was not statistically different between the two groups. The CINV was completely controlled during overall phase in 58.3% of patients receiving granisetron or palonosetron in combination with a corticosteroid, whereas in 11.1% of those without co-treatment of a corticosteroid (P < 0.05). There were significantly higher frequencies of anorexia, leucopenia and neutropenia in the palonosetron group. There is a statistically significant difference in the frequency of febrile neutropenia between presence and absence of a corticosteroid (p = 0.024). Conclusion These findings suggested that a combination use of a corticosteroid with a 5-HT3 receptor antagonist was preferable for CINV control in patients with Hodgkin lymphoma receiving ABVD therapy, although the careful management of febrile neutropenia is required. Trial registration The study approval numbers in the institution; 24-12 and 24-359. Registered April 17, 2012 and June 21, 2012.